[Rezension von: Gabriela Ramos and Yanna Yannakakis, editors, Indigenous intellectuals] - Brosseder, Claudia (The American historical review, 2015)
The twelve essays in this volume edited by Gabriela Ramos and Yanna Yannakakis on “indigenous intellectuals” in colonial Mexico and the Andes will definitely sp
Gesehen am 02.06.2020
Keywords: Rezension